Thermal analysis of thermoplastic elastomer materials due to electrical tracking phenomena - Abdullah, Zainab (2010)
Thermoplastic Elastomer (TPE) material is a new material in which to be responded into high voltage system application as an outdoor insulation. Polymeric material was found has major advantage in weight reduction compared to ceramic and glass. However, for long time application under environment factors such as wet and contaminated condition, the performance of this material have to be investigated in order to identify their potential. The insulation failure occurs when carbonised tracks bridge between the electrodes. This electrical tracking phenomenon, which is a carbonaceous process, occurs on the surface because of the leakage current flowing on the surface. Based on that, this study was conducted to investigate the thermal behaviour of this material due to tracking under AC voltage. The thermal properties of the thermoplastic elastomer materials has been analysed by thermogravimetry analysis (TGA) and differential scanning calorimetry (DSC). Both techniques measured the material properties of weight changes and heat flows as a function of temperature, respectively. The result shows that the sample experienced tracking test indicates slightly improved on melting temperature. This study indicates that the weight loss and melting temperature of HDPE/ENR-50 with MMT content improved after this sample undergo tracking test.